ANALISIS STRUKTUR ALUR DALAM NOVEL AYAT-AYAT CINTA 2 KARYA HABIBURRAHMAN EL SHIRAZY - Al Idrus, Syarif Zulkarnain; Martono, Martono; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is reviewed by the low level of awareness that there will be knowledge of literary works in a novel that can be used as reference material for implementation plan, literary learning in school, can also be the implementation plan of the spreading (RPP). The results of this study is useful for researchers to increase knowledge in analyzing the works and can be used as learning materials. The theory in this case is called the novel, the plot and also the conflict that has occurred in a literary work. This research uses descriptive method, descriptive form, and using structural approach. The source of this dating data is the novel Ayat ? ayat Cinta 2 works of Habuburrahman El Shirazy. The data in this research is the introduction of the situation secita, the peak of conflict, completion, and comment study. Data processing tool in research is technique used as planner, executor, interpreter, and reporter of result data. Test the validity of data thatresearchers use with observer triangulation method. Keywords: Novel, Structure Flow